Comparison of Kirschner wires and Cannulated screw internal fixation for displaced lateral humeral condyle fracture in children - Thapa, Pabin; Sapkota, Krishna; Wahegaonkar, Krishna; Ranjeet, Niraj; Onta, Pratyenta Raj; Thapa, Upendra Jung (Asian Journal of Medical Sciences, 2019)
Background: Lateral condyle fracture of the distal humerus is the second most common injury around the elbow. Aims and Objective: The purpose of the study was to compare Kirschner wires (K-wire) and Cannulated cancellous (CC) screw for internal fixation of displaced lateral humeral condyle fracture in children. Materials and Methods: Forty-six patients with a displaced lateral condyle fracture of humerus were included in the study. Patients were treated with open reduction and internal fixation either with two 1.8mm K-wires or one 4mm CC screw. Fractures were classified according to Milch classification and clinical outcomes were evaluated according to criteria of Hardacre et al. Results: There were 23 patients in each group with the mean age of 6.57 years (range 2 to 12 years). Milch type II was common (n= 34) than Milch type I (n=12). Fracture union was observed at mean 4.13 weeks in the CC screw and 4.61 weeks in K-wire group.(p value = 0.026). On an average the CC screws were removed at 13.57 weeks and K-wires were at 4.57 weeks. The mean follow-up was 13.83 months in CC screw and 12.52 months K-wire group. Three patients (6.5%) had superficial pin site infection and 2 patient (4.3%) had lateral condyle prominence in the K-wire group and only one lateral condyle prominence (2.2%) was observed in the CC screw group. According to the Hardacre et.al criteria CC screw group were excellent in 20 (87%) and good in 3 (13%) patients whereas 13 (56.5%) excellent and 10 (43.5%) good results were found in the K-wire group. (p value = 0.022). Conclusion: Open reduction and internal fixation with either K-wires or cannulated cancellous screw for displaced lateral condyle fracture of humerus are both effective treatment methods but screw fixation provides absolute stability at the fracture site enhancing the fracture healing, reduces the probability of lateral prominence and allows early range of motion and activity in the affected elbow.